2012
DOI: 10.1038/leu.2012.119
|View full text |Cite|
|
Sign up to set email alerts
|

Cereblon is a direct protein target for immunomodulatory and antiproliferative activities of lenalidomide and pomalidomide

Abstract: Thalidomide and the immunomodulatory drug, lenalidomide, are therapeutically active in hematological malignancies. The ubiquitously expressed E3 ligase protein cereblon (CRBN) has been identified as the primary teratogenic target of thalidomide. Our studies demonstrate that thalidomide, lenalidomide and another immunomodulatory drug, pomalidomide, bound endogenous CRBN and recombinant CRBN–DNA damage binding protein-1 (DDB1) complexes. CRBN mediated antiproliferative activities of lenalidomide and pomalidomide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
626
2
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 697 publications
(692 citation statements)
references
References 34 publications
31
626
2
10
Order By: Relevance
“…This is consistent with in vitro data demonstrating antimyeloma effects of POM on LEN-resistant MM cell lines. 25,26 These results support the use of immunomodulatory agents in succession, and show that prior LEN treatment should not preclude the use of POM.…”
supporting
confidence: 55%
“…This is consistent with in vitro data demonstrating antimyeloma effects of POM on LEN-resistant MM cell lines. 25,26 These results support the use of immunomodulatory agents in succession, and show that prior LEN treatment should not preclude the use of POM.…”
supporting
confidence: 55%
“…Similar to lenalidomide and pomalidomide, which bind to CRBN, a critical component of a ubiquitin E3 CRL4 CRBN complex (120,121), CC-220 binds to CRBN to promote recruitment of Ikaros and Aiolos to CRL4 CRBN and the subsequent enhancement of the ubiquitination and degradation of these transcription factors (55-57). Ikaros and Aiolos are members of the Ikaros family of zinc-finger transcription factors crucial for the function of mature B cells in the periphery, and required for the generation and survival of high-affinity bone marrow plasma cells (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell activation | CRBN | Kv1.3 | calcium flux | potassium flux R ecent studies have identified cereblon (CRBN) as a thalidomidebinding protein (1,2). CRBN is expressed in the cytoplasm, nucleus, and peripheral membranes of a wide variety of cells and tissues (1,(3)(4)(5).…”
mentioning
confidence: 99%